2016
DOI: 10.3892/ijo.2016.3635
|View full text |Cite
|
Sign up to set email alerts
|

The resveratrol analogue, 3,4,5,4′-trans-tetramethoxystilbene, inhibits the growth of A375 melanoma cells through multiple anticancer modes of action

Abstract: Resveratrol is a natural dietary product that has demonstrated multifaceted anticancer activity. Several analogues of resveratrol have been synthesized in an effort to enhance the pharmacological potency and improve the pharmacokinetic properties of the compound. 3,4,5,4'‑trans‑tetramethoxystilbene (3,4,5,4'‑TMS) is a methoxylated analogue of resveratrol that has demonstrated anti-proliferative activity in vitro (in cancer cell lines) and in vivo (in xenograft models). In the present study, the anticancer effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In the recent years, considerable attention has been given to synthetic resveratrol derivatives, and numerous studies have reported that methoxylated, hydroxylated, and halogenated derivatives display more effective disease prevention characteristics than resveratrol . RV01 is the quinolyl‐substituted derivative of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, considerable attention has been given to synthetic resveratrol derivatives, and numerous studies have reported that methoxylated, hydroxylated, and halogenated derivatives display more effective disease prevention characteristics than resveratrol . RV01 is the quinolyl‐substituted derivative of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considerable attention has been given to the structural modification of resveratrol. In the recent years, many resveratrol derivatives have been developed to serve as functional food ingredients and supplements to promote health and prevent disease . ( E )‐5‐(2‐(Quinolin‐4‐yl) vinyl) benzene‐1,3‐diol (RV01), a novel quinolyl‐substituted derivative of resveratrol, was also designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, the 3,4,5,4'-trans-tetramethoxystilbene (TMS) was reported as the most potent pro-apoptotic analog of resveratrol (reviewed in [75]).…”
Section: Resveratrol and Cancermentioning
confidence: 99%
“…Thus far, the results from preclinical studies using resveratrol have failed to be replicated in humans, possibly due to the short half‐life, low bioavailability in vivo and lipophilic nature of resveratrol . To improve bioavailability and antimelanomagenesis activity, synthetic resveratrol derivatives and nanoformulations are now being explored as chemopreventive agents to prevent melanoma . A recent study by Sanna et al .…”
Section: Dietary Agentsmentioning
confidence: 99%
“…Thus far, the results from preclinical studies using resveratrol have failed to be replicated in humans, possibly due to the short half-life, low bioavailability in vivo and lipophilic nature of resveratrol (111,112). To improve bioavailability and antimelanomagenesis activity, synthetic resveratrol derivatives and nanoformulations are now being explored as chemopreventive agents to prevent melanoma (113)(114)(115)(116)(117). A recent study by Sanna et al found that chitosan-and anionic alginate-coated poly(d, l0lactide-co-glycolide (PLGA) nanoparticles were able to preserve bioactivity of resveratrol up to 6 months and allow for a controlled release formulation (118).…”
Section: Resveratrolmentioning
confidence: 99%